2008
DOI: 10.1016/j.schres.2008.01.027
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism of the metabotropic glutamate receptor mGluR7 (GRM7) gene is associated with schizophrenia

Abstract: Introduction: Glutamate dysfunction has been implicated in the pathophysiology of schizophrenia. The metabotropic glutamate receptors (mGluRs) are G-protein-coupled receptors. GRM7, the gene that encodes mGluR7, is expressed in many regions of the human central nervous system. The GRM7 gene is located on human chromosome 3p26, which has been suggested by linkage analysis to contain a susceptibility locus for schizophrenia. Methods:We screened for mutations in all exons, exon/intron junctions, and promoter regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 25 publications
2
41
2
1
Order By: Relevance
“…Studied variant (rs17603876) is in LD with rs12155594, associated with transition to psychosis (Bousman et al, 2013). GRM7 variant, rs3864075, has been associated with cognitive phenotype in the Clinical Antipsychotic Trials of Intervention Effectiveness (CATIE) study (Need et al, 2009), and its other variants were reported to be associated with schizophrenia (Ohtsuki et al, 2008;Ganda et al, 2009;Shibata et al, 2009). GRM7, a metabotropic glutamate receptor is implicated in glutamate signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Studied variant (rs17603876) is in LD with rs12155594, associated with transition to psychosis (Bousman et al, 2013). GRM7 variant, rs3864075, has been associated with cognitive phenotype in the Clinical Antipsychotic Trials of Intervention Effectiveness (CATIE) study (Need et al, 2009), and its other variants were reported to be associated with schizophrenia (Ohtsuki et al, 2008;Ganda et al, 2009;Shibata et al, 2009). GRM7, a metabotropic glutamate receptor is implicated in glutamate signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The amphetamine-induced hyperactivity, DOI-induced head twitch, and CAR tests in rodents have been shown to be sensitive to typical and atypical antipsychotic drugs (Ellenbroek, 1993;Wettstein et al, 1999;Wadenberg, 2010). The rationale for testing ADX71743 in models of psychosis, in part, came from several independent studies showing a link between polymorphisms in mGlu 7 and schizophrenia (Ohtsuki et al, 2008;Ganda et al, 2009;Shibata et al, 2009). ADX71743 resulted in a dose-dependent, albeit modest, reduction of amphetamine-induced hyperactivity in mice.…”
Section: Discussionmentioning
confidence: 99%
“…As such, dysregulation of mGluR7 has been linked to many psychiatric diseases including depression (Bradley et al, 2011;Cryan et al, 2003), anxiety (Fendt et al, 2008;Mitsukawa et al, 2006), schizophrenia (Bolonna et al, 2001;Ohtsuki et al, 2008) and drug addiction Li et al, 2009Li et al, , 2010. In rodents, results have indicated that the mGluR7 allosteric agonist N,N'-dibenzyhydryl-ethane-1,2-diamine dihydrochloride (AMN082) dose dependently inhibits cocaine-induced enhancement of electrical brainstimulation reward and intravenous cocaine self-administration in rats ).…”
Section: Introductionmentioning
confidence: 99%